Presence of human noroviruses on bathroom surfaces: a review of the literature. Issue 4 (3rd July 2016) - Leone, Cortney M.; Tang, Chaoyi; Sharp, Julia; Jiang, Xiuping; Fraser, Angela
Abstract: Enteric viruses are the most common cause of acute gastroenteritis worldwide with most cases of illness attributed to caliciviruses, such as human noroviruses (HuNoV). While environmental transmission of HuNoV is reported to be low, environmental surfaces could be a source of secondary transmission. As many vomiting/fecal episodes occur in bathrooms, bathroom surfaces could be an important vehicle for transmitting HuNoV. We systematically reviewed the literature to determine the presence of HuNoV on bathroom surfaces. Our review included 22 eligible studies conducted in commercial and institutional settings. Under outbreak conditions, 11 studies reported detection rates of 20–100 %. Six studies implicated bathroom surfaces as primary sources of HuNoV infection while three reported HuNoV present on bathroom surfaces but indicated different primary sources. Under non-outbreak conditions, five studies reported detection rates of 2–17 %. Factors associated with HuNoV presence in bathrooms included population density, setting type, employee numbers, food handler knowledge, awareness, and behaviours, and cleaning/disinfecting procedures. Our review suggests bathrooms could be vehicles that transmit HuNoV under both outbreak and non-outbreak conditions.